Cluster survey evaluation of a measles vaccination campaign in Jharkhand, India, 2012. - Heather M Scobie; Arindam Ray; Satyabrata Routray; Anindya Bose; Sunil Bahl; Stephen Sosler; Kathleen Wannemuehler; Rakesh Kumar; Pradeep Haldar; Abhijeet Anand (PLoS ONE)
Introduction India was the last country in the world to implement a two-dose strategy for measles-containing vaccine (MCV) in 2010. As part of measles second-dose introduction, phased measles vaccination campaigns were conducted during 2010-2013, targeting 131 million children 9 months to <10 years of age. We performed a post-campaign coverage survey to estimate measles vaccination coverage in Jharkhand state. Methods A multi-stage cluster survey was conducted 2 months after the phase 2 measles campaign occurred in 19 of 24 districts of Jharkhand during November 2011-March 2012. Vaccination status of children 9 months to <10 years of age was documented based on vaccination card or mother's recall. Coverage estimates and 95% confidence intervals (95% CI) for 1,018 children were calculated using survey methods. Results In the Jharkhand phase 2 campaign, MCV coverage among children aged 9 months to <10 years was 61.0% (95% CI: 54.4-67.7%). Significant differences in coverage were observed between rural (65.0%; 95% CI: 56.8-73.2%) and urban areas (45.6%; 95% CI: 37.3-53.9%). Campaign awareness among mothers was low (51.5%), and the most commonly reported reason for non-vaccination was being unaware of the campaign (69.4%). At the end of the campaign, 53.7% (95% CI: 46.5-60.9%) of children 12 months to <10 years of age received ≥ 2 MCV doses, while a large proportion of children remained under-vaccinated (34.0%, 95% CI: 28.0-40.0%) or unvaccinated (12.3%, 95% CI: 9.3-16.2%). Conclusions Implementation of the national measles campaign was a significant achievement towards measles elimination in India. In Jharkhand, campaign performance was below the target coverage of ≥ 90% set by the Government of India, and challenges in disseminating campaign messages were identified. Efforts towards increasing two-dose MCV coverage are needed to achieve the recently adopted measles elimination goal in India and the South-East Asia region.